Identidade, territorialidade e o processo de regularização fundiária da comunidade quilombola de Mituaçu - PB - Filgueira, Débora Louise (2020)
The recognition of the right to land for the Remaining Quilombos Communities is ensured under the terms of art. 68 of the Transitional Constitutional Provisions Act - ADCT of the Federal Constitution of 1988. Despite the significant legislative advance, several legal, political and governmental strategies, marked by structural racism, lead to the State's inability to promote land regularization in these territories. The struggles involving the realization of this right reveal the colonial structures of exercise of power present in the State and in its organs, Executive, Legislative or Judiciary, which seek to devalue the trajectories of resistance that these communities have led to have their rights guaranteed. In this context, the present study aims to analyze the strengthening of ethnic identity and quilombola autonomy from the process of land regularization in Mituaçu - PB. It’s specific objectives are: to study the process of building the subjects' identity and ethnic territoriality, to analyze the effectiveness of public policies, national and local, of territorial development, how they interfere the structure of the quilombola territory and also to evaluate the mobilization and political participation residents in claiming their land. The work brings a discussion about constitutional protection to the territory, considering it as a Human Right for Traditional Communities. The theoretical-methodological construction of the analysis is based on the humanistic cultural approach influenced by the critical theory of knowledge. The research was anchored in qualitative data based on the bibliographic and documentary review, based on interdisciplinarity, since it searches in several scientific fields, such as Geography, Law, Sociology and Anthropology, for its foundation. We conducted fieldwork and semi-structured interviews, in addition to photographic, audio and field notebooks to reinforce the understanding of the territorial dynamics and the struggle for land in Mituaçu - PB. We conclude that the process of land regularization of Mituaçu, despite the inumerous dificulties it faces, appears as a “new” element that has aroused in some residents the need to reaffirm their histories, not only in an inert movement to recall historical facts, but of build new dynamics and interpretations about their identities and their territories, involving processes of resignification from an awareness about racism, the modes of oppression and legal, social and economic invisibility to which they were subjected for centuries, allowing them to create an identity in the discordant sense of the colonial logic, from a critical conception that has made this process of political struggle for land to make possible relationships and interactions between the group in order to guarantee its autonomy.